Phase-Variable Changes in the Position of O-Methyl Phosphoramidate Modifications on the Polysaccharide Capsule of Campylobacter jejuni Modulate Serum Resistance - Pequegnat, Brittany (J Bacteriol, 2017)
Campylobacter jejuni polysaccharide capsules (CPS) are characterized by the presence of nonstoichiometric O-methyl phosphoramidate (MeOPN) modifications. The lack of stoichiometry is due to phase variation at homopolymeric tracts within the MeOPN transferase genes. C. jejuni strain 81-176 contains two MeOPN transferase genes and has been shown previously to contain MeOPN modifications at the 2 and 6 positions of the galactose (Gal) moiety in the CPS. We demonstrate here that one of the two MeOPN transferases, encoded by CJJ81176_1435, is bifunctional and is responsible for the addition of MeOPN to both the 2 and the 6 positions of Gal. A new MeOPN at the 4 position of Gal was observed in a mutant lacking the CJJ81176_1435 transferase and this was encoded by the CJJ81176_1420 transferase. During routine growth of 81-176, the CJJ81176_1420 transferase was predominantly in an off configuration, while the CJJ81176_1435 transferase was primarily on. However, exposure to normal human serum selected for cells expressing the CJJ81176_1420 transferase. MeOPN modifications appear to block binding of naturally occurring antibodies to the 81-176 CPS. The absence of MeOPN-4-Gal resulted in enhanced sensitivity to serum killing, whereas the loss of MeOPN-2-Gal and MeOPN-6-Gal resulted in enhanced resistance to serum killing, perhaps by allowing more MeOPN to be put onto the 4 position of Gal. IMPORTANCE Campylobacter jejuni undergoes phase variation in genes encoding surface antigens, leading to the concept that a strain of this organism consists of multiple genotypes that are selected for fitness in various environments. Methyl phosphoramidate modifications on the capsule of C. jejuni block access of preexisting antibodies in normal human sera to the polysaccharide chain, thus preventing activation of the classical arm of the complement cascade. We show that the capsule of strain 81-176 contains more sites of MeOPN modifications than previously recognized and that one site, on the 4 position of galactose, is more critical to complement resistance than the others. Exposure to normal human serum selects for variants in the population expressing this MeOPN modification.